An innovative sensor for hydroxylamine determination: Using molybdenum hybrid zeolitic imidazolate framework–conducting polymer composite as electrocatalyst. (10th December 2019) - Liang, Cuiyuan; Zhang, Feng; Lin, Huiming; Jiang, Cheng; Guo, Wei; Fan, Songjie; Qu, Fengyu
Abstract: A novel composite material, hybrid zeolitic imidazolate framework (HZIF)–conducting poly(3, 4-ethylenedioxythiophene) (PEDOT) has been fabricated on carbon cloth electrode (CCE) by microwave-assisted crystallization, followed by drop-coating and vapor deposition procedures. Specifically, the HZIF inserted by molybdenum (HZIF-Mo) is entitled to intrinsic catalytic activity towards amine molecules, which is firstly integrated with the conductive and catalytic PEDOT as an enhanced electrochemical sensor for hydroxylamine. Detection is performed by amperometric method, and the composite sensor (HZIF-Mo/PEDOT/CCE) shows a low detection limit of 0.04 μM (S/N = 3) in the linear range of 0.1–692.2 μM, along with superior anti-interference ability, reproducibility (RSD = 4.43%) and outstanding performance in real samples. As noticed, the hydroxylamine catalytic process combines the advantages of the alkaline-stable HZIF-Mo containing ample catalytic sites and high surface area and the mesoporous PEDOT reining in outstanding conductivity and redox capability, thereby imparting amplified electrochemical signals. This work undertakes an opening to expand MOF-based composites for versatile sensing applications. Graphical abstract: Image 1 Highlights: HZIF-Mo is firstly and highly crystallized by microwave-assisted technique. Catalytically active MoO4 blocks in HZIF-Mo avails to hydroxylamine oxidation. HZIF-Mo/PEDOT/CCE sensor combines the merits of porous HZIF and conducting polymer. The sensor displays low detection limit and good performance in real detection. This study extends HZIFs materials applied in electrochemistry.